Chemical Composition, Antioxidants, Antibacterial, and Insecticidal Activities of Origanum elongatum (Bonnet) Emberger & Maire Aerial Part Essential Oil from Morocco - Imane Tagnaout; Hannou Zerkani; Noureddine Bencheikh; Smail Amalich; Mohamed Bouhrim; Ramzi A. Mothana; Mohammed R. Alhuzani; Rachid Bouharroud; Christophe Hano; Touriya Zair (MDPI AG, 2023)
The aim of this research is to profile the chemical composition of the essential oil (EO) extracted from the aerial parts of Origanum elongatum (O. elongatum) and to evaluate its antioxidant, antibacterial and insecticidal activities on Ceratitis capitata adults. Gas chromatography coupled with mass spectrometry (GC/MS) revealed a total of 27 constituents in EO of O. elongatum, which accounted for 99.08% of its constituents. Carvacrol (57.32%) was a main component, followed by p-cymene (14.70%) and γ-terpinene (9.84%). The antioxidant activity of O. elongatum EO was investigated using DPPH (1,1-diphenyl-2-picrylhydrazyl), FRAP (Ferric reducing antioxidant power), and TCA (the total antioxidant capacity) methods. This EO exhibited a remarkable antiradical and reducing power against DPPH (IC50 = 2.855 ± 0.018μL/mL), FRAP (EC0.5 = 0.124 ± 0.013µL/mL) and TCA (IC50 = 14.099 ± 0.389 mg AAE/g of the EO). The antibacterial tests in vitro, using the disc and dilution methods, were carried out on nine pathogenic bacteria isolated from the hospital patients, such as Enterococcus faecalis, Serratia fonticola, Staphylococcus aureus, Acinétobacter baumannii, Klebsiella oxytoca, Klebsiella pneumoniae sensible, E.coli sensible, E.coli resistante, and Enterobacter aerogenes. The EO demonstrated a considerable antibacterial activity with minimum inhibitory concentrations (MIC) from 2 to 8 µL/mL against all strains except Staphylococcus aureus (MIC = 32 µL/mL). Regarding the insecticidal activity, the fumigation test indicated a high efficacy (100% mortality), and a lethal dose of LD50  =  17 ± 0.53 μL/L air was found after 24 h of exposureTherefore, O. elongatum EO could be utilized as a natural antioxidant, antibiotic and biopesticides.